Zeolites and related materials : trends, targets and challenges : proceedings of the 4th International FEZA Conference, Paris, France, 2-6 September 2008 /: trends, targets and challenges : proceedings of the 4th International FEZA Conference, Paris, France, 2-6 September 2008. (2008) - Unknown
No abstract available